Amphibian traits database: A global database on morphological traits of amphibians. Issue 5 (11th March 2023) - Huang, Na; Sun, Xinyuan; Song, Yanfang; Yuan, Zhiyong; Zhou, Weiwei
Abstract: Motivation: Amphibians are a diverse vertebrate group with more than 8, 000 species, which is an important part of major terrestrial and freshwater ecosystems. Unfortunately, amphibians are experiencing a worldwide population decline. Trait information is important for understanding the causes of endangerment. Additionally, such information is essential for ecological and evolutionary studies using trait‐based approaches. However, such data are scarcer for amphibians than for any other terrestrial vertebrate groups. To fill this gap, we collected morphological traits of global amphibians available from the literature and compiled a database to facilitate future studies. Main types of variables contained: Forty‐two morphological traits of Anura, 27 morphological traits of Caudata and 37 morphological traits of Gymnophiona. Spatial location and grain: Global. Major taxa: Amphibia. Level of measurement: Species. Software format: .csv.